A conformation and charge co-modulated ultrasensitive biomimetic ion channel. Issue 84 (3rd October 2016) - Cai, Sheng-Lin; Zheng, Yu-Bin; Cao, Shuo-Hui; Cai, Xiu-Hong; Li, Yao-Qun
Abstract : For the first time, an ultrasensitive nanopore-based sensor that co-modulated simultaneously by conformation and charge has been developed for the detection of ATP. Abstract : For the first time, a biomimetic ion channel co-modulated simultaneously by conformation and charge using a single stimulus has been demonstrated, and, based on the synergetic effect of this channel, an ultrasensitive nanopore sensor for ATP with a limit of detection down to sub-pM was developed.